Antecedents of Interest and the Investment of Fluid Intelligence in the Formation of Crystalized Intelligence - Ganzach, Yoav (Frontiers in Psychology, 2021)
Most of the studies of the effects of fluid intelligence and non-cognitive characteristics on crystalized intelligence examined additive effects. The results of the few studies that examined interactive effects are inconsistent. Some find a positive (facilitating) interaction and some find a negative (compensatory) interaction. We improve on these previous studies by examining non-cognitive characteristics that were not studied before and by using a very large representative sample (n=11266) We find a positive/facilitating interaction. We discuss the implication of these results to theories about the joint effect of fluid intelligence and non-cognitive characteristics on crystalized intelligence.